Private Investment in Independent Film: Attraction Strategies and Risk Management - Mariia Demydenko (Scientific Trends, 2025)
This article analyzes the specifics of attracting private investment into independent film production, as well as risk management strategies specific to this segment of the film industry. Key approaches to minimizing financial and reputational risks are explored. Particular attention is paid to the role of social media and international collaboration in increasing the attractiveness of independent film projects to private investors.
Keywords: Private investment, independent film, investment attraction strategies, risk management, film production, international cooperation.